2014
DOI: 10.1177/1077559514560625
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment Among U.S. Air Force Parents Deployed in Support of Operation Iraqi Freedom/Operation Enduring Freedom

Abstract: This study examined child maltreatment perpetration among 99,697 active-duty U.S. Air Force parents who completed a combat deployment. Using the deploying parent as the unit of analysis, we analyzed whether child maltreatment rates increased postdeployement relative to predeployment. These analyses extend previous research that used aggregate data and extend our previous work that used data from the same period but used the victim as the unit of analysis and included only deploying parents who engaged in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…129 Children of deployed US military personnel have higher rates of emotional and behavioral problems and substance abuse 130,131 and are at a higher risk for physical abuse and neglect both during and after parental return from deployment. [131][132][133]…”
Section: Children With Remote Exposure To Armed Conflictmentioning
confidence: 99%
“…129 Children of deployed US military personnel have higher rates of emotional and behavioral problems and substance abuse 130,131 and are at a higher risk for physical abuse and neglect both during and after parental return from deployment. [131][132][133]…”
Section: Children With Remote Exposure To Armed Conflictmentioning
confidence: 99%
“…Studies among U.S. military personnel have documented increased rates of physical abuse and neglect in the children of veterans, both during the period of deployment and after return. [96, 97] A large study of Californian children in civilian public schools found that the children of US military personnel have higher rates of experiencing violence in school and are more likely to carry a weapon. [98]…”
Section: Resultsmentioning
confidence: 99%
“…This is a concerning, since research shows rates of child maltreatment by female civilian spouses triple when soldiers are deployed (Panton, 2018). Rates of neglect and emotional abuse are even higher postdeployment (Rabenhorst et al, 2015).…”
Section: Discussionmentioning
confidence: 99%